2009
DOI: 10.1111/j.1751-7176.2009.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Risk of Incident Hypertension Among Men

Abstract: The independent association between insulin resistance and the development of hypertension remains in doubt because insulin resistance correlates with other metabolic factors also proposed to be associated with hypertension. The authors examined the association between the insulin sensitivity index and incident hypertension in a prospective nested case-control study among 1453 men (mean age, 61 years) who participated in the Health Professionals' Follow-up Study. The authors computed the insulin sensitivity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
2
5
1
Order By: Relevance
“…Furthermore, our finding of statistically significant interaction with age for the association between hypertension and T2DM can be ascribed to the evidence that hypertension increases with age and is also concordant with previous studies among different population groups [ 38 , 39 ]. For example, in a prospective study among the US population [ 39 ], Lai et al [ 39 ], showed a positive interaction with age for the association between insulin sensitivity index and incident hypertension. Similar findings were reported among the Chinese population, in a study by Wan et al [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, our finding of statistically significant interaction with age for the association between hypertension and T2DM can be ascribed to the evidence that hypertension increases with age and is also concordant with previous studies among different population groups [ 38 , 39 ]. For example, in a prospective study among the US population [ 39 ], Lai et al [ 39 ], showed a positive interaction with age for the association between insulin sensitivity index and incident hypertension. Similar findings were reported among the Chinese population, in a study by Wan et al [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…It is unclear, however, in the current study as in previous observational studies [ 38 , 39 ] if the associations observed are causal. Although a meta-analysis of prospective studies by Emodin et al [ 40 ] postulates that participants with elevated HBP are at increased risk of T2DM, longitudinal studies among populations from the UK [ 41 ], China [ 38 ], and the US [ 42 ], showed that T2DM may be in the causal pathway of hypertension whereas the opposite was not likely.…”
Section: Discussioncontrasting
confidence: 53%
“…[43][44][45] ). However, not insulinemia alone but insulin resistance is usually related to blood pressure in prehypertensive and hypertensive patients and it is able to predict incident hypertension [46][47][48] . There was not found correlation between insulin levels and BP in the present study, too.…”
Section: Discussionmentioning
confidence: 99%
“…There is a dearth of data on the relations of insulin resistance measures and incident BP changes and among Blacks; with prior studies conducted in samples with no or a very limited number of Black individuals [7][8][9][10][11][12][13][14][15][16]. To our knowledge, no prior study has assessed the relation of insulin resistance and longitudinal BP changes in a sample made exclusively of Blacks.…”
Section: Introductionmentioning
confidence: 99%